3-D numerical modelling of greenwater loading on fixed ship-shaped FPSOs. (January 2019) - Chen, Lifen; Taylor, Paul H.; Draper, Scott; Wolgamot, Hugh
Abstract: This work is focused on the assessment of greenwater overtopping onto fixed ship-shaped FPSO models using three dimensional (3-D) Computational Fluid Dynamics (CFD) simulations. Good agreement between the numerical results and published experimental data from Barcellona et al. (2003) indicates that 3-D CFD is an effective tool which may be used to assess greenwater associated with an incident wave group. Different wall-sided bow shapes are investigated numerically, and the results provide insight into how the bow shape influences the evolution of on-deck flows, and the horizontal force on a vertical wall spanning the full deck width for incident waves approaching normal to the bow. It is found that the horizontal force, thus, the horizontal momentum of greenwater flows, is a result of the combined action of water-front velocities and the corresponding water volume impacting on the structures. For the bow shapes considered in this study, although clear differences in on-deck flow are observed for different bow shape, differences in force on the vertical wall are relatively small. Simulations for a 2-D vertical rectangular box that has the same longitudinal section as the 3-D model FPSOs give somewhat similar results to 3-D predictions along the centre-line. This similarity may be due partly to the fact that increases in on-deck flow velocity due to increased freeboard exceedance in the 2-D simulations compensates for a lack of focusing of the on-deck flow observed in the 3-D simulations. This finding has implications for understanding how computationally cheaper 2-D greenwater simulations relate to more realistic 3-D greenwater events. Highlights: CFD modelling is an effective tool for assessing greenwater events for FPSOs. Good agreement between numerical and published experimental results is obtained. The effect of wall-sided bow shape on greenwater loading has been investigated. Both water-front velocities and the water volume on the structure are important. The associated force on deck structures depends on the 3-D bow shape. Nevertheless, the difference in the peak force is small for the bow shapes studied. Both the freeboard exceedance and the focusing of on-deck flows are important.